DEVELOPMENT OF DIGITAL BOOK ON SHORT STORY MATERIALS IN INDONESIAN LANGUAGE LESSONS - Himmatul Khairoh As; Mustaji; I Wayan Arsana (Institute of Computer Science (IOCS), 2022)
The purpose of this development is this development is to produce a Digital Book as an interesting source of information with Indonesian language subject matter so that it can improve student learning outcomes in doing exercises in Indonesian lessons. The development process involves subject matter experts, learning design experts and learning media experts to provide feedback and suggestions for improvement. In addition, the Indonesian language teacher as a user of this Digital Book also provided feedback and input. The use of Borg & Gall's Digital Book Development for Indonesian subjects can effectively increase active learning interactions. The results of this development research are that this Digital Book Product has a material feasibility level, learning design feasibility, and learning media feasibility. While the level of small group trials and field trials with qualifications is very feasible and does not need to be revised.